PENGARUH PENGGUNAAN BIG DATA ANALYTICS DAN KINERJA AUDITOR TERHADAP KUALITAS AUDIT - Muhammad, Nur Fulki; Astuti Rahayu, Puji (Universitas Katolik Parahyangan, 2024)
In the digital era 4.0, technology is something that is needed by humans in supporting human activities. The rapid development of technology encourages a fast and precise way of working, with technology being a necessity for auditors in carrying out the audit process. One of the technological developments created is Big Data Analytics which can help the auditor's work in the hope that it can help the audit process which can produce good audit quality. However, in addition to Big Data Analytics, auditor performance is also needed Auditors deal with various types of data. In this case, auditors are needed to process data and check whether the financial statements are in accordance with applicable standards. In the Digital 4.0 era, processing various types of data requires technology and also requires the ability of auditors. And it is hoped that the use of Big Data Analytics and auditor performance can produce good audit quality. This research uses quantitative methods. Samples were taken from Public Accounting Firms (KAP) located in Indonesia using purposive sampling. The data was processed using the IBM SPSS Statistics version 27 program, with 31 respondents. The results of this study explain that when the Big Data Analytics and auditor performance variables are reviewed partially on audit quality, the results Big Data Analytics and auditor performance have a significant effect on audit quality. Recommendations that can be given are that auditors must utilize the use of Big Data Analytics and improve good performance so that the resulting audit quality is also good